Mosquito species and outdoor breeding places in residential areas in Malaysia - Saleeza, S.N.R.; Norma-Rashid, Y.; Sofian-Azirun, Mohd (2013)
We conducted mosquito surveillance at outdoor breeding habitat in 459 households at 7 urban locations in Putrajaya, Malaysia from January to December 2010 to determine the predominant species and breeding locations. The most common species found at all locations was Aedes albopictus. Gardening utensils were the most common breeding sites. Of the 1,885 mosquito larvae specimens found, 1,774 (94.1) were Ae. albopictus larvae, 84 (4) were Ae. aegypti larvae and 27 (1) were Culex quinquefasciatus larvae. The Aedes index for each of the locations was higher than the goal set by the Ministry of Health for Malaysia. However, the container index at each of the locations was within the goal. The Breateau index was above the goal set by the Ministry of Health at Precinct 9B1 but the other locations were within the goal.